Theo van Leeuwen’s Exclusion and Inclusion Strategies: An Analysis of President Joe Biden’s Political Speech - Merni Handayani; Budi Eko Pranoto (English Literature Study Program, Faculty of Arts and Education Universitas Teknokrat Indo, 2023)
The researcher conducted research to find out how the process of exclusion and inclusion in very important topic that is happening at this time regarding the speech made by President Joe Biden as the President of the United States to criticize the actions of the Russian state which attacked the State of Ukraine.This study uses a qualitative descriptive method with Discourse Analysis approach through the theory proposed by Theo van Leeuwen to describe how the social actors are described in the speech delivered by President Joe Biden. In President Joe Biden's speech, 13 data were found that were used to marginalize the social actors, namely the Russian government which carried out attacks on Ukrainian state.In this study, no exclusion strategy was found, but four inclusion strategies were found, namely Differentiation – Indifferentiation, Assimilation – Individualization, Objectivation – Abstraction and Association – Disassociation. The most dominant inclusion strategy found was Differentiation – Indifferentiation with the percentage of 50%. Meanwhile for Objectivation – Abstraction and Assimilation – Individualization are 12,5%, while the percentage of Association – Disassociation is 25% were found. Key words: Critical Discourse Analysis, Exclusion, Inclusion Strategies and Joe Biden’s Political Speech.